2011
DOI: 10.1021/jf2032473
|View full text |Cite
|
Sign up to set email alerts
|

Corn Mint (Mentha arvensis) Extract Diminishes Acute Chlamydia pneumoniae Infection in Vitro and in Vivo

Abstract: Corn mint ( Mentha arvensis ) provides a good source of natural phenols such as flavone glycosides and caffeic acid derivatives, which may have prophylactic properties against inflammations. This study investigated whether corn mint extract would be beneficial against a universal respiratory tract pathogen, Chlamydia pneumoniae , infection. The extract inhibited the growth of C. pneumoniae CWL-029 in vitro in a dose-dependent manner. The inhibition was confirmed against a clinical isolate K7. The phenolic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…The studies on calcium channel blockers indicate that their administration to C . pneumoniae -infected macrophages rescue the infection from persistence and results in a more productive infection, and similarly, our observations on applying nonspecific (verapamil) or L-type specific (isradipin) calcium channel blockers to infected epithelial cells support the view that these compounds activate rather than suppress the acute infection [11]. The impact of phenolic compounds on L-type channel mediated Ca 2+ influx varies depending on compound structure [49,50].…”
Section: Plant Phenolics As Antichlamydial Agentssupporting
confidence: 64%
See 2 more Smart Citations
“…The studies on calcium channel blockers indicate that their administration to C . pneumoniae -infected macrophages rescue the infection from persistence and results in a more productive infection, and similarly, our observations on applying nonspecific (verapamil) or L-type specific (isradipin) calcium channel blockers to infected epithelial cells support the view that these compounds activate rather than suppress the acute infection [11]. The impact of phenolic compounds on L-type channel mediated Ca 2+ influx varies depending on compound structure [49,50].…”
Section: Plant Phenolics As Antichlamydial Agentssupporting
confidence: 64%
“…In this model, treatment with luteolin significantly decreased the bacterial load in the lungs and antibody titers in the bloodstream, but also diminished the inflammatory changes in histological samples of the lung [13]. Similar results have also been obtained with a phenol-rich extract of corn mint [11]. …”
Section: Plant Phenolics As Antichlamydial Agentssupporting
confidence: 55%
See 1 more Smart Citation
“…Both the mint extracts and pure compounds exhibited high levels of inhibitory activity in vitro, with low host cell toxicity. In a mouse model, intraperitoneally administered corn mint extracts delivered at nutritionally relevant concentrations resulted in reduced inflammatory symptoms but were not as effective as antibiotics in clearing the infection [53]. Kapp et al, performed an in vitro study on the effect of seven peppermint ( Mentha × piperita L.) tea extracts on C. pneumoniae -infected human cells.…”
Section: Biomedical Phytochemical Groups and Anti-infective Actionmentioning
confidence: 99%
“…Mentha arvensis belongs to the family Lamiaceae and is famous for its therapeutic and medicinal values since prehistoric times. It has been reported in various studies that plant extracts of Mentha have been found to possess bioactive ingredients that showed antioxidant, antifungal and antibacterial activities [6].…”
mentioning
confidence: 99%